Nurses Knowledge about Comminuted Fracture in Baghdad Teaching Hospitals - Ammar Zghair; Hussein Atiyah (Kufa Journal for Nursing Sciences)
Background: Infection control for patients with comminuted fracture is one of the most common healthcare-associated infections. The infection control can help reduce to post-operative morbidity, prolonged recovery, delayed discharge and increasing cost. Nurses’ knowledge of the evidence-based recommendations is necessary to provide high-quality nursing care.